Biobrane™ and skin staples: beware of necrotic ulceration. Issue 5 (14th January 2015) - Hyland, Ela J; Maze, Deborah; Lawrence, Torey; Harvey, John G; Holland, Andrew JA
Abstract: Biobrane™ is a product used for temporary wound coverage post major paediatric burn wound debridement. We report two cases of necrotic ulceration associated with the use of Biobrane™ with skin staples. We suggest securing Biobrane™ with alternatives such as adhesive tapes and glue to prevent the occurrence of this adverse outcome.